1985
DOI: 10.2337/diacare.8.5.418
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Relative Blood Glucose Response of Mixed Meals Using the White Bread Glycemic Index

Abstract: Unexpected plasma glucose responses to different mixed meals fed to normal and diabetic volunteers have recently been reported. We have therefore examined in normal volunteers the effect of mixing carbohydrate foods of different glycemic indices (GIs) without the addition of fat and protein. The observed GI of the mixed meal was within 2% of the expected value. In studies in the literature where fat and protein were added to mixed meals, the observed blood glucose responses also related significantly to the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 0 publications
5
68
1
Order By: Relevance
“…The method also affected the statistical evaluation, as the difference between the postprandial responses following the two meals was clearer when the change from the fasting values was used (significant at 15 (p<0.05), 30 (p<0.02) and 45 min (p < 0.01)). Furthermore, use of the glycaemic index, which accounts for the positive incremental area [1], yields a lower inter-subject variation [26]. The importance of the method of calculation for the interpretation of postprandial glucose levels has been pointed out earlier by Gannon and Nuttall [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method also affected the statistical evaluation, as the difference between the postprandial responses following the two meals was clearer when the change from the fasting values was used (significant at 15 (p<0.05), 30 (p<0.02) and 45 min (p < 0.01)). Furthermore, use of the glycaemic index, which accounts for the positive incremental area [1], yields a lower inter-subject variation [26]. The importance of the method of calculation for the interpretation of postprandial glucose levels has been pointed out earlier by Gannon and Nuttall [27].…”
Section: Discussionmentioning
confidence: 99%
“…High and varying blood glucose fasting values have been shown to be disturbing factors in the evaluation of effects from different meals [25]. This is supported by a negative correlation between the preprandial blood glucose level and the glycaemic response [26]. Reduced renal excretion of excess glucose due to a lack of water may partially explain the late postprandial hyperglycaemia following the test meal without added water in the group of poorly-controlled diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting the rate of glucose absorption from starchy food and therefore the GI value include (1) the nature of the food and (2) the type and extent of food processing (Table 5). The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Low GI foods include vegetables, fruit, legumes and wholegrain breads such as pumpernickel, while high-GI foods include most refined grain products such as white bread, potatoes and rice (Table 2). The GI tables may have various applications, for instance in designing diets aimed at long-term blood glucose control, as some researchers have found that the GI may be applied not only to single foods but also to mixed meals (Wolever et al, 1985;Chew et al, 1985;Collier et al, 1986;Bornet et al, 1987;Le Floch et al, 1991). The GI of mixed meals has also been shown to correlate positively with the insulinemic index (a measure of postprandial insulin rise; Bornet et al, 1987).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…The glycaemic response to cooked rice has been extensively investigated (O'Dea et al, 1980;Wolever et al, 1985;Brand Miller et al, 1992;Rasmussen et al, 1992;Casiraghi et al, 1993;Larsen et al, 1996), but large variations in the ®ndings have led to disagreements as to whether rice should be considered a high or low glycaemic food. It is now increasingly accepted that the large differences in the glycaemic response to rice are in part due to variations in the physico-chemical properties of rice varieties as well as in the processing.…”
Section: Introductionmentioning
confidence: 99%